Integrating interactive video media in physical education: a study on critical thinking and learning motivation - Silva Ayu Trisnawati; Mochamad Ridwan; Edi Setiawan; Farruh Ahmedov (Edu Sportivo)
Background: At present, the process of physical education learning has incorporated the use of video-based interactive media, with the aim of optimising the achievement of learning outcomes. However, to the best of our knowledge, there remains a notable gap in research that explores the application of video-based interactive media in enhancing critical thinking and fostering greater interest in learning among students, particularly through mixed-method research. Research Objective: The aim of this study is to examine the impact of video-based interactive media on the development of critical thinking skills and the enhancement of students’ interest in learning physical education in junior high schools within Surabaya City. Methods: This study utilised a mixed-methods approach, with a research sample comprising 33 eighth-grade students who were divided into two groups: an experimental group (n = 17) using media-based learning and a control group (n = 16) employing traditional teaching methods. The research instruments included a critical thinking questionnaire, an interest in learning survey, and in-depth interviews to gather qualitative data. Finding/Results: Statistical analysis showed a significant increase in students’ critical thinking skills in the experimental group; the average post-test score increased to 59.1 (p < 0.05), while the control group showed 55.0. Thus, students’ interest in learning increased to 95.6 (p < 0.05), while the control group increased to 98.1. Qualitative findings showed that students using video-based interactive media expressed greater interest and demonstrated increased critical thinking due to the interactive and flexible nature of visual presentations. However, challenges related to technology access, such as reliance on internet connectivity and network stability, were identified as limiting factors. Conclusion: Our research confirms that involving video-based interactive media learning is an effective way to change critical thinking skills and interest in learning among students. This study contributes important information for teachers so that they can use video-based interactive media learning programs continuously in the future.